E-Consultation for Skincare Products via Intelligent Agent Technology - Jamaluddin, Malinie (Universiti Teknologi Petronas, 2006)
Intelligent Agent technologies are becoming viable solutions to many problems related to E-commerce technologies that are not as user friendly as they seem. The skincare industry is continuously serving customer through consultation by humans. However, human beings have limited capability in fulfilling one's request. With these being said, this Final Year Project focuses on finding an intelligent agent that provides electronic consultation for the skincare industry. The main objective of this project is to create a flexible consultation environment for skincare's customers. This will result in a higher level of satisfaction and experience just like the current system. The methodology used for this project is the waterfall development-based technique which comprises of requirements analysis and definition, system design, implementation and testing, verification and maintenance. The tools used are Macromedia Dreamweaver MX, Adobe Photoshop, Pandorabots free web hosting, Oddcast Inc.'s VHost™, AIML, Apache Web Server and PHP. Based on the work carried out, it is found that although the usage of agent technology is a natural evolution of e-commerce, to effectively build and deliver an agent technology into an e-commerce websites requires rethinking and re-evaluating the human-computer interaction in the new environment. Second round of surveys were conducted to help determining whether users will be interested in the technology. It is found that the conceptof an Agent Technology might be an interest to users, provided it can assist them in consultation process. Agent Technology will be even easily acceptable if it is able to provide almost the same consultation experience based on the current consultation style, and able to provide an interactive discussion environment to users. Those who disagree prefer to stick to current style or might reject technology changes. Users are very concern with the reliability of the system as this will be the main factor whether the information provided by the agent technology is reliable or not. As a conclusion, more researches are expected to be carried out by technologists to further understand the acceptance on an agent technology and thus implementing it in various industries throughout the world.